Pengaruh Fixed Asset Turnover. Current Ratio, dan Debt to Equity Ratio terhadap Price To Earnings Ratio pada PT.Wijaya Karya Tbk - Rudi Sanjaya; Alvina Ghalda; Hasan Rifa’i; Pipih Apiliani (Anggaran : Jurnal Publikasi Ekonomi dan Akuntansi, 2024)
This research aims to determine the influence of Fixed Asset Turnover, Current Ratio, and Debt to Equity Ratio on Price to Earnings Ratio at PT. Wijaya Karya Tbk. Period 2012-2023. PT. Wijaya Karya Tbk. Is a construction company listed on the Indonesian Stock Exchange (BEI). This research recommends more efficient management of fixed assets and liquidity to improve company performance, the fixed asset turnover ratio reflects the efficiency of using fixed assets in a company to generate income, the current ratio represents the company's ability to meet short-term obligations, and the debt to equity ratio and shows the company's financial structure and influences the financial risks provided. This research method uses SPSS with the classic assumption test, t test and F test and from this research it results that Fixed Asser Turnover and Current Ratio have a strong influence on the Price to Earnings Ratio and Debt to Equity Ratio which have no influence on the Price to Earnings Ratio, and this research suggests further research by adding other variables to broaden the analysis.